Hydrogen Borrowing: towards Aliphatic Tertiary Amines from Lignin Model Compounds Using a Supported Copper Catalyst. Issue 19 (24th August 2022) - Ruijten, Dieter; Narmon, Thomas; De Weer, Hanne; van der Zweep, Robbe; Poleunis, Claude; Debecker, Damien P.; Maes, Bert U. W.; Sels, Bert F.
Abstract: Upcoming biorefineries, such as lignin‐first provide renewable aromatics containing unique aliphatic alcohols. In this context, a Cu‐ZrO2 catalyzed hydrogen borrowing approach was established to yield tertiary amine from the lignin model monomer 3‐(3, 4‐dimethoxyphenyl)‐1‐propanol and the actual lignin‐derived monomers, (3‐(4‐hydroxyphenyl)‐1‐propanol and dihydroconiferyl alcohol), with dimethylamine. Various industrial metal catalysts were evaluated, resulting in nearly quantitative mass balances for most catalysts. Identified intermediates, side and reaction products were placed into a corresponding reaction network, supported by kinetic evolution experiments. Cu‐ZrO2 was selected as most suitable catalyst combining high alcohol conversion with respectable aliphatic tertiary amine selectivity. Low pressure H2 was key for high catalyst activity and tertiary amine selectivity, mainly by hindering undesired reactant dimethylamine disproportionation and alcohol amidation. Besides dimethylamine model, diverse secondary amine reactants were tested with moderate to high tertiary amine yields. As most active catalytic site, highly dispersed Cu species in strong contact with ZrO2 is suggested. ToF‐SIMS, N2 O chemisorption, TGA and XPS of spent Cu‐ZrO2 revealed that imperfect amine product desorption and declining surface Cu lowered the catalytic activity upon catalyst reuse, while thermal reduction readily restored the initial activity and selectivity demonstrating catalyst reuse. Abstract : Tertiary amines from lignin model monomers : A heterogeneous Cu‐ZrO2 catalyzed hydrogen borrowing strategy was developed to synthesize tertiary amines from lignin (model) monomers. Reusability of the easily recoverable catalyst was investigated by recycle experiments and in depth analysis of the spent catalyst (ToF‐SIMS, N2 O chemisorption, XPS and TGA). Thermal reduction proved to be an efficient catalyst regeneration strategy.